QUEUING MODEL DESIGN TO OPTIMIZE FOR PRE FLIGHT SERVICES DURING THE COVID-19 PANDEMIC. (Case Study At Sultan Hasanuddin International Airport Makassar) - Faisal Halim; Sapta Asmal; Kifayah Amar (Center for Study and Journal Management FTI UMI, 2022)
This study aims to determine (1) the optimal timing for flight service users before making a flight (pre flight) at Sultan Hasanuddin International Airport Makassar. (2) The optimal standard time during the Pre Flight process during the Covid-19 pandemic at Makassar Sultan Hasanuddin International Airport, and (3) Efforts made by airport managers in minimizing pre flight processing time.This study uses the Flow Process Chart method which is a schematic/diagram depiction that shows all the steps in a program and shows how the steps interact with each other.Based on the results of the analysis, it is concluded that: the optimal time for Pre Flight Services activities at Sultan Hasanuddin International Airport Makassar is not in accordance with the standards that refer to the Decree of the Director General of Civil Aviation where the standard time is still high; the optimal time required for the Pre Flight Services process is 20 minutes 40 seconds for normal time and the standard time is 23 minutes 37 seconds; As for the efforts made to minimize pre-flight processing time, including improving the quality of human resources on duty, increasing airport capacity, correcting infrastructure, regular maintenance of the equipment used and maximizing service at the check-in counter, especially during peak loads